Spectroscopic OCT by Grating-Based Temporal Correlation Coupled to Optical Spectral Analysis - L. Froehly; M. Ouadour; L. Furfaro; P. Sandoz; P. Leproux; G. Huss; V. Couderc (International Journal of Biomedical Imaging)
Spectroscopic optical coherence tomography (spectroscopic OCT) is an echographic-like optical method for biomedical functional imaging. Current spectroscopic optical coherence tomography (OCT) methods rely on a posteriori numerical calculation. We present an alternative for optically accessing the spectroscopic information in OCT, that is, without postprocessing, by using a grating-based correlation and a wavelength demultiplexing system. Spectrally resolved A-scan is directly recorded on the image sensor. Due to the grating-based system, no correlation scan is necessary. The signal is registered in the wavelength-depth plane on a 2D camera that provides a large number of resolved points. In the frame of this paper, we present the principle of the system as well as demonstration results. Advantages and drawback of this system compared to others are discussed.